Aplikasi Metoda Taguchi Untuk Mengetahui Optimasi Kebulatan Pada Proses Bubut Cnc - Sidi, Pranowo; Wahyudi, Muhammad Thoriq (Jurnal Rekayasa Mesin, 2013)
In this paper surface optimization for the surface roundness has been done by considering the cutting parameters as cutting speed, feed rate and depth of cut. The experiments were performed on a CNC lathe, and the materials used for the experiment is steel St.60, with 100 mm length and 1" diameter. For design and optimize the results experiments used Taguchi method, and to predict the level of significance tests that contribute to the unity of the surface is done by ANOVA with Minitab 15 software. From this research the optimized values contributing as cutting speed 60 m/menit, feed 0.2 mm/rev and depth of cut 0,125 mm respectively. To find out the extent to which the accuracy of the minimum values of surface roundness, then do validation on parameter values corresponding to the optimization of the minimum value of the parameter.Keywords: roundness, cutting speed, feeding, depth of cut, Taguchi.